Women's perception of support and control during childbirth in The Gambia, a quantitative study on dignified facility-based intrapartum care - Saffie Colley; Chien-Huei Kao; Meeiling Gau; Su-Fen Cheng (BMC, 2018)
Abstract Background In The Gambia, a woman faces 1 in 24-lifetime risk of maternal death due to pregnancy and childbirth, yet, only 57% of deliveries are conducted by skilled birth attendants. However, poor provider attitude has been identified as one of the contributing factors hampering the efforts of the government in improving access to skilled care during childbirth. This study, therefore, explored women's perception of support and control during childbirth in The Gambia. Methods A descriptive cross-sectional study was employed. A convenience sampling method was used to select participants in two regions in The Gambia. A sample size of 200 women who met the eligibility criteria was recruited after informed consent. The demographic-obstetric information sheet and the Support and Control in Birth scale (SCIB) were used to collect data. Data analysis was done using SPSS software version 23.0. Results Women's perceptions of support and control were low. External control 1.85 (SD ± 0.43) recorded the least perception compared to internal control 2.41 (SD ± 0.65) and perception of support 2.52 (SD ± 0.61). Participants reported the lowest perceptions in pain control, involvement in decision making, information sharing and the utilization of different position during birth. Women's age (p < .001) and mode of delivery (p = .01), significantly predicted women's perception of internal control. Educational status (p = .02), mode of delivery (p = .04), place of delivery (p < .001) and perception of support (p < .001) significantly predicted women's perception of external control, whilst birth plan (p = .001), mode of delivery (p = .04), and perception of external control (p < .001) significantly predicted women's perception of support. Conclusion This study concluded that an environment that promotes women feeling a sense of control and support during childbirth should be created in order to ensure a dignified intrapartum care in The Gambia. This can be achieved through effective training of skilled birth attendants on non-pharmacological pain management, effective communication with clients and promoting women's participation in decision-making regarding their care throughout the process of childbirth.